Environmental Citizen Science for Environmental Citizenship: An Educational Innovation in Biology and Environmental Education for Green Transition and Sustainable Development - Hadjichambis, Andreas Ch.; Hadjichambi, Demetra; Georgiou, Yiannis (My University, 2025)
The current environmental and climate crisis the entire planet is experiencing calls for urgent and necessary innovations in order to achieve a sustainable future as well as a green transition. Environmental citizen science initiatives are considered an important innovation that can contribute to these goals. However, despite the assumed benefits of participation in environmental citizen science, many of them are designed to address merely scientific questions often adopting a more science-oriented rather than a citizen-centered approach. This chapter examines the current conditions of citizen participation and inclusion as well as barriers and exclusion factors. It also focuses on how citizens’ participation in environmental Citizen Science initiatives contributes to the Education for Environmental Citizenship, as a venue through which citizens can undertake actions in different scales (local, national, global) to achieve environmental citizenship. The chapter concludes with a discussion on how this goal could be achieved through presenting and further elaborating on the Citizen Science for Environmental Citizenship (CS4EC) framework. The CS4EC framework may contribute to expanding citizens’ (including students’) participation from mere data collection activities in the process of co-designing citizen science initiatives, and therefore, in decision-making regarding crucial socio-environmental issues, as well as in action-taking in private and public spheres towards environmental and social change.